2019
DOI: 10.1093/pm/pnz267
|View full text |Cite|
|
Sign up to set email alerts
|

A Dyadic Perspective on Coping and its Effects on Relationship Quality and Psychological Distress in Couples Living with Chronic Pain: A Longitudinal Study

Abstract: Objective Dyadic coping is a process of coping within couples that is intended not only to support the patient with chronic pain but also to maintain equilibrium in the relationship. This study aims to investigate the effect of patient-perceived and spouse-reported dyadic coping on both the patient and their partner’s relationship quality and anxiety, stress, and depression over time. Methods One hundred thirty-nine couples, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 39 publications
0
14
1
Order By: Relevance
“…In fact, engaging in less hostile, superficial, or ambivalent behaviours is expected to have positive implications for the dyadic adjustment of the partner. However, and contrary to this hypothesis and to research demonstrating a negative association between negative DC and dyadic adjustment (Mittinty et al, 2020;Regan et al, 2014;Traa et al, 2015), we also found that for HIV-uninfected partners, higher negative DC was associated with higher cohesion. In the literature, some studies have shown that negative interactions between partners can improve romantic relationships in the long run because such interactions may help lead the partners to better understand the relationship challenges and each other's needs (Gottman & Krokoff, 1989;Li & Fung, 2013).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In fact, engaging in less hostile, superficial, or ambivalent behaviours is expected to have positive implications for the dyadic adjustment of the partner. However, and contrary to this hypothesis and to research demonstrating a negative association between negative DC and dyadic adjustment (Mittinty et al, 2020;Regan et al, 2014;Traa et al, 2015), we also found that for HIV-uninfected partners, higher negative DC was associated with higher cohesion. In the literature, some studies have shown that negative interactions between partners can improve romantic relationships in the long run because such interactions may help lead the partners to better understand the relationship challenges and each other's needs (Gottman & Krokoff, 1989;Li & Fung, 2013).…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to our second hypothesis, the aggregated measure of positive DC by oneself was not significantly associated with the dyadic adjustment of any partner. Although some studies have found a positive link between positive DC behaviours, namely, supportive DC, and the dyadic adjustment of couples in which one member was dealing with a chronic 12 condition (Mittinty et al, 2020;Regan et al, 2014), our findings are similar to those reported in a study with couples facing breast cancer that did not find any significant associations between supportive or delegated DC and relationship quality (Rottmann et al, 2015). As also verified by Rottmann et al (2015), this lack of significance seems to reinforce the importance and centrality of common DC for the adjustment of HIV-serodiscordant couples over the positive DC behaviours provided by one partner.…”
Section: Discussionmentioning
confidence: 98%
“…A growing body of research emphasizes the major psychological effects of chronic illnesses on partners [e.g. 17 21 ]. Hudson et al [ 22 ] highlight the opportunity of dyadic analysis in capturing the social and relational implications of health and illness on social networks—and its consequences of being a source of support or additional stress.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, couples may be taught communication skills to discuss threats to the helping process, such as goal conflict experienced by partners, and to foster dyadic coping with pain 34 . For instance, ICPs may be taught to clearly communicate their needs to their partner.…”
Section: Discussionmentioning
confidence: 99%